Effects of composite restorations on oxidative stress in saliva: An in vivo study - Pinar Gul; Nilgun Akgul; Hamit Hakan Alp; Ahmet Kiziltunc (Journal of Dental Sciences, 2015)
Background/purpose: This study is aimed at detecting and quantifying monomers from dental composite filling materials and investigating effects of the released monomers in saliva malondialdehyde (MDA) levels and in two antioxidant enzyme levels after dental composite filling materials were applied to healthy volunteers. Materials and methods: Fifty-two individuals (32 female and 20 male) participated in the research study. Saliva samples were collected in scheduled time intervals and MDA, superoxide dismutase, and glutathione peroxidase levels were measured. In addition, saliva samples were collected in order to quantify triethyleneglycol dimethacrylate, hydroxyethyl methacrylate, bisphenol-A diglycidyl methacrylate, and urethane dimethacrylate using high-performance liquid chromatography. Statistical analysis of obtained data was performed by repeated measures variance analysis. A P value <0.05 was considered as statistically significant. Results: As a result of the statistical analysis, the MDA and glutathione peroxidase levels measured at all time intervals were significantly higher when compared to the baseline levels (P < 0.05). Superoxide dismutase values measured after 7 days showed a statistically significant decrease (P < 0.001). The residual monomer levels showed a significant increase within 7 days, and the maximum amount of release was observed generally in the 7-day period, and the release in monomers except for bisphenol-A diglycidyl methacrylate showed a significant decrease in 30 days (P < 0.05). Conclusion: Because of monomer release after the restoration process and also differences in antioxidant enzyme activity, composite materials may lead to oxidative stress.